Alcohol drinking, tobacco smoking and subtypes of haematological malignancy in the UK Million Women Study. - Kroll, M; Murphy, F; Pirie, K; Reeves, G; Green, J; Beral, V (2012)
BACKGROUND: Previous research suggests associations of lower alcohol intake and higher tobacco consumption with increased risks of haematological malignancy. The prospective Million Women Study provides sufficient power for reliable estimates of subtype-specific associations in women. METHODS: Approximately 1.3 million middle-aged women were recruited in the United Kingdom during 1996-2001 and followed for death, emigration and cancer registration until 2009 (mean 10.3 years per woman); potential risk factors were assessed by questionnaire. Adjusted relative risks were estimated by Cox regression. RESULTS: During follow-up, 9162 incident cases of haematological malignancy were recorded, including 7047 lymphoid and 2072 myeloid cancers. Among predominantly moderate alcohol drinkers, higher intake was associated with lower risk of lymphoid malignancies, in particular diffuse large B-cell lymphoma (relative risk 0.85 per 10 g alcohol per day (95% confidence interval 0.75-0.96)), follicular lymphoma (0.86 (0.76-0.98)) and plasma cell neoplasms (0.86 (0.77-0.96)). Among never- and current smokers, higher cigarette consumption was associated with increased risk of Hodgkin lymphoma (1.45 per 10 cigarettes per day (1.22-1.72)), mature T-cell malignancies (1.38 (1.10-1.73)) and myeloproliferative/myelodysplastic disease (1.42 (1.31-1.55)). CONCLUSION: These findings confirm and extend existing evidence for associations of subtypes of haematological malignancy with two common exposures in women.